A companion to Greco-Roman and late antique Egypt - Vandorpe, Katelijn (John Wiley & Sons, Inc, 2019)
2.4 Conclusion: A Bright FutureFurther Reading; Part II Egypt as part of a globalizing world; Chapter Three The Last Pharaohs: The Ptolemaic Dynasty and the Hellenistic World; 3.1 Ptolemy I and the Foundation of the Ptolemaic Dynasty (323-305/4 BC); 3.2 The Legitimization of Power: The Ptolemies as Hellenistic Kings and as Pharaohs; 3.3 The Golden Age (305/4-204 BC); 3.4 Crises and Reorganization (204-116 BC); 3.5 116-80 BC: A Transitional Period; 3.6 The Ptolemies and Rome (80-30 BC); 3.7 Conclusion; Further Reading; Chapter Four A Roman Province in the Eastern Mediterranean
Keywords: 332 B.C.-638 A.D; Egypt -- Civilization -- 332 B.C.-638 A.D; Egypt -- History -- 332-30 B.C; Égypte - Civilisation - 332 av. J.-C.-640; Égypte - Histoire - 332-30 av. J.-C; Electronic books; Aufsatzsammlung; Geschichte 323 v. Chr.-500; Ägypten